STUDI KARAKTERISTIK MARSHALL PADA CAMPURAN ASPAL PANAS (AC-WC) DENGAN VARIASI RENDAMAN OLI BARU KENDARAAN TRUCK TRAILER - Idayani Idayani; Kumita Kumita; Zia Ulfata (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Road pavement plays a critical role in ensuring smooth transportation flow and supporting regional economic growth, particularly in areas with high traffic volumes and heavy vehicle loads. This study investigates the effect of immersion duration in new truck-trailer engine oil on the Marshall characteristics of Asphalt Concrete–Wearing Course (AC-WC) mixtures. An experimental method was conducted in the Asphalt Pavement Laboratory of the Faculty of Engineering, Universitas Almuslim, using Pen 60/70 asphalt, well-graded aggregates, and new heavy-vehicle oil as the immersion medium. The optimum asphalt content (OAC) obtained from preliminary Marshall testing was 5.74% and was applied to all test specimens. The specimens were immersed in new oil for 0, 10, 20, 30, and 40 minutes before undergoing Marshall tests, including stability, flow, Marshall Quotient (MQ), density, Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), and Voids Filled with Asphalt (VFA). The results show that stability values increased with longer immersion durations, with the highest stability recorded at 40 minutes (1300 kg), all of which met the 2014 Bina Marga technical specifications. Flow values for all variations remained within the standard range (2–4 mm), indicating adequate plastic deformation resistance. MQ values exhibited a rising trend as immersion time increased, suggesting greater stiffness and structural resistance. Meanwhile, density values tended to increase, while VIM values decreased, demonstrating reduced air voids due to oil penetration. VMA and VFA parameters generally met the required specifications, confirming that the AC-WC mixture maintained acceptable performance under oil exposure. Overall, the findings indicate that immersion in new engine oil can enhance the mechanical properties of AC-WC mixtures, particularly in terms of stability and stiffness, without violating established specifications. This suggests that AC-WC mixtures retain their structural performance even under oil contamination conditions typically encountered in heavy-vehicle operational areas.